Locus of Control and Non-Adaptive Coping in Postpartum Depression: A Prospective Study with Maternal Competence as a Buffer - Lorena Gutiérrez-Hermoso; Patricia Catalá-Mesón; Carmen Écija-Gallardo; Cecilia Peñacoba-Puente (IMR Press, 2024)
Background: Pregnancy can be a stressful time that affects a woman's health, potentially leading to postpartum depression (PPD). Research has highlighted the importance of certain cognitive variables in coping with depressive symptoms. Specifically, among mothers, the perception of maternal competence has been shown to be a protective factor against postpartum depression. Conversely, other variables such as external locus of control (ELoC), have been identified as risk factors, although the research in this area is less abundant. It would be valuable to explore the role of an external locus of control through integrative models that consider its possible interactions throughout pregnancy and postpartum. The aim of the present study was to evaluate the relationship between the external locus of control (at the beginning of pregnancy) and postpartum depression (four months after childbirth), with emotional coping as a mediating variable and maternal competence as a moderating variable. Methods: A prospective cohort study was conducted with 120 pregnant women recruited from a public hospital in Madrid, Spain. External locus of control was assessed by Rotter's locus of control scale during the first-trimester of pregnancy, non-adaptive emotional coping was assessed by Coping Strategies Questionnaire (CAE) during the third-trimester of pregnancy, and postpartum depression was assessed by Edinburgh Postnatal Depression scale and perceptions of maternal competence were evaluated by Mother and Baby Scale, both during the puerperium. Multivariate regression analyses were conducted using a moderated mediation model, controlling for anxiety and depression. Results: Results showed a significant mediating effect of emotional coping between external locus of control and postpartum depression. The effect of external locus of control on postpartum depression, considering the effect of emotional coping, was statistically significant (direct effect: β = 4.73, t = 1.23, p = 0.006, [95% confidence interval (CI) = 1.24/2.39]). The effect of maternal competence as a moderator within the mediation model was also significant (total effect: c = 0.351, t = 2.37, p = 0.020, [95% CI = 0.057/0.064]). Regarding covariates, a significant effect of depressive symptoms on moderation-mediation model was observed (β = 5.57, t = 3.49, p = 0.009, [95% CI = 2.38/8.75]). The moderated mediation model, including maternal competence as a moderator, suggested that the relationship between external locus of control on postpartum depression, mediated by emotional coping, varied across different levels of maternal competence (β = -0.150, [95% CI = -0.0188/-0.241]), indicating buffering effects at medium (β = -0.195, p = 0.002) and high (β = -0.258, p < 0.001) levels of maternal competence. Prenatal anxious-depressive symptoms (covariates) did not exhibit significant effects on the proposed moderated mediation model. Conclusions: External locus of control predicts potential risk for postpartum depression through the use of maladaptive emotional coping strategies. The effect can be diminished by perceptions of maternal competence in infant care. Prenatal emotional symptoms no predict postpartum depression when maternal competence is considered. Therefore, promoting maternal competence can serve as a positive resource for reducing postpartum depression and supporting the adaptive transition of a woman's identity within the maternal role.